ECOLOGY OF THE WATERS AROUND THE ISLANDS OF THE CASPIAN SEA - M. A. Salmanov; G. F. Hasanov (Юг России: экология, развитие)
Aim. The study of the ecology of the offshore Islands of the Caspian sea.Location. Islands in the Caspian sea. Methods. Applied modern biological, microbiological and chemical methods. Results. Since 2000 in the waters of most of the Islands marked increase in the primary production of phytoplankton. At the same time restoring a previous fauna-flora in them is still not observed.Main conclusions. Ecosystem numerous Islands Absheron Baku archipelago underwent a big change that first debt had a negative impact on the natural development of the faunaflora, trophic relationships and circulation of substances as the basis for the formation of the overall biological productivity in large areas of the shelf of the Caspian sea.